Handling low haemoglobin and iron deficiency in a blood donor population. (29th January 2016) - Magnussen, K.; Ladelund, S.
Abstract : Background: Blood donors with low haemoglobin concentration (Hb) and iron deficiency are well‐known challenges in any blood bank setting. The handling of such donors is complex, and although iron deficiency is a frequent cause of anaemia, there are differential diagnoses. Aims: The primary aims were to standardize and optimize the handling of blood donors with Hb below the limit for donation. Secondary aims were to deal with all issues related to high or low either Hb or ferritin in blood donors. Methods: The problem was approached by centralizing measurement of Hb, initiating ferritin measurements and establishing Centre for Donor Haemoglobin and Iron. An algorithm was created, taking Hb and ferritin into account. The donors were mainly contacted by post, but when Hb was low or when there was insufficient effect of previously given iron supplementation, the donors were contacted by phone to improve compliance. Hb was measured on Sysmex‐XE2100D at every donation. Ferritin was measured once in all donors, at every 10th donation and repeated when outside 60–300  μ g/l or Hb low at the previous donation. Results: February 1st 2012–February 1st 2015, 71 450 donors (53·5%women/46·5%men) donated 281 814 units of whole blood. Due to changes in calibration, Hb changes could only be monitored over the first 24 months. Mean Hb increased in the female and male donors ( P  < 0·0001). Percentage of donors with low Hb decreased (women OR/month = 0·98; P  < 0·0001; men OR/month = 0·97; P  < 0·0001). Summary/conclusions: The program of iron supplementation restricted only to those that would benefit has led to an increase in Hb and a reduction in the number of donors with low Hb.